Bioactive effects of graphene oxide cell culture substratum on structure and function of human adipose‐derived stem cells. Issue 12 (24th April 2013) - Kim, Jangho; Choi, Kyoung Soon; Kim, Yeonju; Lim, Ki‐Tack; Seonwoo, Hoon; Park, Yensil; Kim, Deok‐Ho; Choung, Pill‐Hoon; Cho, Chong‐Su; Kim, Soo Young; Choung, Yun‐Hoon; Chung, Jong Hoon
<x xml:space="preserve">Abstract</x> Nanoscale topography of artificial substrates can greatly influence the fate of stem cells including adhesion, proliferation, and differentiation. Thus the design and manipulation of nanoscale stem cell culture platforms or scaffolds are of great importance as a strategy in stem cell and tissue engineering applications. In this report, we propose that a graphene oxide (GO) film is an efficient platform for modulating structure and function of human adipose‐derived stem cells (hASCs). Using a self‐assembly method, we successfully coated GO on glass for fabricating GO films. The hASCs grown on the GO films showed increased adhesion, indicated by a large number of focal adhesions, and higher correlation between the orientations of actin filaments and vinculin bands compared to hASCs grown on the glass (uncoated GO substrate). It was also found that the GO films showed the stronger affinity for hASCs than the glass. In addition, the GO film proved to be a suitable environment for the time‐dependent viability of hASCs. The enhanced differentiation of hASCs included osteogenesis, adipogenesis, and epithelial genesis, while chondrogenic differentiation of hASCs was decreased, compared to tissue culture polystyrene as a control substrate. The data obtained here collectively demonstrates that the GO film is an efficient substratum for the adhesion, proliferation, and differentiation of hASCs. © 2013 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 101A: 3520–3530, 2013.